Participatory Rurral Appraisal Based Restoration in Support of Restoration of Degraded Peat Ecosystems in Tanjung Leban Village Bengkalis - Resdati; Yusuf, Yusmar; Sidiq, Rd. Siti Sofro (International Journal of Educational Research & Social Sciences, 2021)
Restoration based on Participatory rural appraisal is applied as the main carrying capacity for the successful restoration of peat ecosystems. This program is implemented through the approach of Rewetting, Revegeation and Revitalization. The research objective analyzes PRA-based restoration efforts and how the move will proceed. The data is obtained through interviews and analyzed qualitatively descriptively. The study found that peat wetting activities were carried out through the construction of canal barriers and supporting infrastructure, while replanting was implemented in line with economic revitalization programs. Not only forest timbers, food crops including pineapples are cultivated as an alternative source of livelihood. Women's groups are encouraged to actively process economic products, namely pineapple dodol and pineapple juice. The program is successful but marketing has not been maximal. The study found that peat wetting activities were carried out through the construction of canal barriers and supporting infrastructure, while replanting was implemented in line with economic revitalization programs. Not only forest timbers, food crops including pineapples are cultivated as an alternative source of livelihood. Women's groups are encouraged to actively process economic products, namely pineapple dodol and pineapple juice. The program is successful but marketing has not been maximal.